Theoretical and numerical analysis of very high harmonic superconducting tunnel junction mixers - Kittara, P; Withington, S; Yassin, G (2007)
We describe a procedure for modeling the nonlinear, quantum-mechanical behavior of very high harmonic superconductor-insulator-superconductor (SIS) mixers. A typical mixer is pumped by a strong microwave source at 10-15 GHz, which causes high-harmonic (20-40) currents to flow, any one of which can be used as a local oscillator to downconvert a submillimeter-wave signal to a low microwave frequency, 1-8 GHz. This mode of operation is attractive for measuring the beam patterns of conventional SIS mixers, because only a single submillimeter-wave source is needed. We conducted simulations using the 20th harmonic of a 13.5 GHz microwave source, downconverting a 271.4 GHz signal to a 1.4 GHz intermediate frequency. These simulations clearly show that linear downconversion can be achieved even for relatively high levels of rf signal power; although, care is needed when choosing the operating point. The patterns of behavior seen in the simulations are in remarkable agreement with recently published experimental results. © 2007 American Institute of Physics.